Literature Review: Implementation of Musharakah Mutanaqisah Partnership Over the World - Wiwin Juliyanti; Yohanes K. Wibowo (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2021)
Purpose: This study aimed to determine the implementation of the musharakah mutanaqisah. Research Methodology: This research method was literature study with data obtained from previous research and theories relevant to the research topic. Results: The research results show that musharakah mutanaqisah in the two countries still needs to be encouraged for its development, because it is still dominated by Murabahah, Ba'i, ijarah and others financing, the results of the study also conclude that the implementation of musharakah mutanaqisah is equally an alternative in property financing in Malaysia, and home ownership loans in Indonesia. Conclusions: This study concludes that musharakah mutanaqisah is a viable Sharia-compliant contract for property financing, although its implementation remains limited and requires stronger regulatory and practical development. Limitations: This research only examined the application of Musharakah Mutanaqisah Partnership (MMP) in Southeast Asia. Contributions: Findings contribute that internationally, the accounting for musharakah mutanaqisah refers to International Financial Reporting Standards (IFRS) and Financial Accounting Standards (FAS). In Malaysia, the regulations governing the accounting for musharakah mutanaqisah are regulated in Malaysian Financial Reporting Standards (MFRS).